Effects on Physicochemical and Microbiological Properties of Coconut Water Packaged in Silver-Based Materials - Malafatti, João Otávio Donizette; da Costa Brito, Sabrina [UNESP]; Pereira, Vinicius Alex Cano; Calisto, Ítalo; Netto, Saad Barbar; Formigoni, Carlos Eduardo; Innocentini, Murilo Daniel de Mello; Mitsuyuki, Milene Corso; Sivieri, Kátia [UNESP]; Ferreira, Marcos David [UNESP] (Wiley, 2025)
Coconut water is a fresh and popular drink that is attractive to consumers worldwide. Packaging development is essential to improve product quality, protect against microorganism contamination and preserve their physical-chemistry properties. Silver nanoparticles (AgNPs) are excellent actives applied in studies of food packaging, exhibiting great antimicrobial activity and reinforcement properties in polymeric matrices. The current work goals are to evaluate AgNPs supported on carriers, silica (SiO2) and hydroxyapatite (Hap) in the linear low-density polyethylene (LLDPE) polymer obtained nanocomposite materials (LLDPE/AgNPs) to coconut water packaging. Thus, the present assay ascertained if adding these active agents in a commercial material (LLDPE) may improve coconut water's physicochemical and microbiological characteristics. The processing obtained the packaging composites at two concentrations (0.4% and 0.6%) by extrusion methodology. The pasteurized coconut water was packaged and monitored during 35 days of storage at temperatures above the recommended (7°C). The physicochemical analyses of coconut water verified the maintenance of pH, titratable acidity, soluble solids content, colour, turbidity, phenolic compounds, antioxidant activities, reducing and nonreducing sugars and minerals. Microbiological analyses were performed to detect the growth of psychrotrophic, moulds and yeasts, enterobacteria and Salmonella spp. The results showed that the AgNPs supported in both particles did not affect coconut water's physical and chemical characteristics compared to the LLDPE control. Concerning microbial growth, adding particles reduced the product's microbial load. Thus, the LLDPE/AgNPs packages obtained in this work demonstrated a potential application as commercial material to coconut water that can preserve the intrinsic physicochemical and improve the microbiological quality.
Keywords: antimicrobial; coconut water; food packaging; nanocomposite; silver nanoparticles